Improving prediction of type 1 diabetes by testing non‐HLA genetic variants in addition to HLA markers. Issue 5 (8th November 2013) - Steck, Andrea K; Dong, Fran; Wong, Randall; Fouts, Alexandra; Liu, Edwin; Romanos, Jihane; Wijmenga, Cisca; Norris, Jill M; Rewers, Marian J
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to explore whether non‐human leukocyte antigen (non‐HLA) genetic markers can improve type 1 diabetes (T1D) prediction in a prospective cohort with high‐risk HLA‐DR, DQ genotypes. Methods The Diabetes Autoimmunity Study in the Young (DAISY) follows prospectively for the development of T1D and islet autoimmunity (IA) children at increased genetic risk. A total of 1709 non‐Hispanic White DAISY participants have been genotyped for 27 non‐HLA single nucleotide polymorphisms (SNPs) and one microsatellite. Results In multivariate analyses adjusting for family history and HLA‐DR3/4 genotype, PTPN22 (rs2476601) and two UBASH3A (rs11203203 and rs9976767) SNPs were associated with development of IA [hazard ratio (HR) = 1.87, 1.55, and 1.54, respectively, all p ≤ 0.003], while GLIS3 and IL2RA showed borderline association with development of IA. INS, UBASH3A, and IFIH1 were significantly associated with progression from IA to diabetes (HR=1.65, 1.44, and 1.47, respectively, all p ≤ 0.04), while PTPN22 and IL27 showed borderline association with progression from IA to diabetes. In survival analysis, 45% of general population DAISY children with PTPN22 rs2476601 TT or HLA‐DR3/4 and UBASH3A rs11203203 AA developed diabetes by age 15, compared with 3% of children with all other genotypes (p < 0.0001). Addition of non‐HLA markers to HLA‐DR3/4, DQ8 did not improve diabetes prediction in first‐degree relatives. Conclusion Addition of PTPN22 and UBASH3A SNPs to HLA‐DR, DQ genotyping can improve T1D risk prediction.